Pengaruh Model Pembelajaran Cinqase Terhadap Kemampuan Berpikir Kritis dan Pemahaman Konsep Titrasi Asam Basa - Dewi, Ida Ayu Ketut Purnama; Siahaan, Jeckson; Muntari, Muntari (Chemistry Education Practice, 2025)
This study aims to reveal the effect of the CINQASE learning model on critical thinking skills and students' conceptual understanding of acid-base titration material at SMAN 6 Mataram. This study is a quantitative study with a quasi-experimental method. The population in this study were students of Phase F Class XI SMAN 6 Mataram. The research sample was taken using the cluster random sampling technique and obtained students of class XI 4 as the control class and students of class XI 3 as the experimental class. The research instrument in measuring critical thinking skills and conceptual understanding was in the form of 5 test questions that had been tested for validity and reliability. The results of the N-Gain values ​​obtained from the experimental class and the control class were analyzed by testing the normality of the N-Gain and homogeneity of the N-Gain first and then testing the hypothesis. Hypothesis testing was carried out using the t-test. The results showed that there was an effect of the CINQASE learning model on students' critical thinking skills and conceptual understanding of acid-base titration material with a significance value of t count > t table. Student responses to the CINQASE model also showed positive results. In conclusion, the CINQASE learning model is effectively applied in chemistry learning to improve critical thinking skills and conceptual understanding.